Poligami Dalam Dawâir Al-Khaūf: Qirâah Fi Khitâb Al-Mar’ah Karya Nasr Hamid Abu Zayd - Syahridawaty Syahridawaty (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2020)
This paper outlines the issue of polygamy according to Nasr Hamid Abu Zayd's perspective with reference to his work namely Dawâir al-Khaūf: Qirâah fi Khiṭâb al-Mar’ah. The purpose of this paper is to describe the biography of Nasr Hamid Abu Zayd, and the book of Dawair al-Khaūf related to the background of book writing, systematic writing, the method used by Nasr Hamid in understanding polygamy verses, and Nasr Hamid's thoughts about polygamy. This paper is the result of a library research, with the main data being the book by Nasr Hamid Abu Zayd. The results showed that Nasr Hamid did not agree with polygamy, even according to him polygamy could be strictly forbidden if there was fear of not being able to do justice. The method initiated by Nasr Hamid Abu Zayd is the method of reading textual (manhaj al-qira’ah as-siyaqiyyah). There are three levels of context in this method, namely the context of revelation (siyaq tartib an-nuzul), narrative context (siyaq as sard), and linguistic structure (mustawa at-tartib al-lughawi).